Adoptive B cell therapy for chronic viral infection - Chung, Young Rock; Dangi, Tanushree; Palacio, Nicole; Sanchez, Sarah; Penaloza-MacMaster, Pablo (Frontiers in Immunology, 2022)
T cell-based therapies have been widely explored for the treatment of cancer and chronic infection, but B cell-based therapies have remained largely unexplored. To study the effect of B cell therapy, we adoptively transferred virus-specific B cells into mice that were chronically infected with lymphocytic choriomeningitis virus (LCMV). Adoptive transfer of virus-specific B cells resulted in increase in antibody titers and reduction of viral loads. Importantly, the efficacy of B cell therapy was partly dependent on antibody effector functions, and was improved by co-transferring virus-specific CD4 T cells. These findings provide a proof-of-concept that adoptive B cell therapy can be effective for the treatment of chronic infections, but provision of virus-specific CD4 T cells may be critical for optimal virus neutralization.